Structural defects in graphene quantum dots: A review - Rabeya R.; Mahalingam S.; Manap A.; Satgunam M.; Akhtaruzzaman M.; Chia C.H. (John Wiley and Sons Inc, 2023)
Energy gap; Graphene; Nanocrystals; Point defects; Structural properties; Surface defects; Edge defects; High surface area; Low toxicity; Method; Preparation process; Property; Stone-Wales defects; Structural defect; Synthesised; Tunable Band-gap; Semiconductor quantum dots